An optimized cocktail of small molecule inhibitors promotes the maturation of dendritic cells in GM-CSF mouse bone marrow culture - Matsuba, Shintaro; Ura, Hiroki; Saito, Fumiji; Ogasawara, Chie; Shimodaira, Shigetaka; Niida, Yo; Onai, Nobuyuki (Frontiers in Immunology, 2023)
Dendritic cells (DCs) are the most potent antigen-presenting cells, playing an essential role in the pathogen and tumor recognition, and anti-tumor immunity, and linking both the innate and adaptive immunity. The monocyte-derived DCs generated by ex vivo culture, have been used for cancer immunotherapy to eliminate tumor; however, the clinical efficacies are not sufficient, and further improvement is essential. In this study, we established a method to generate DCs using small molecule compounds for cancer immunotherapy. We observed an increase in the percentage of CD11c+I-A/I-Ehigh cells, representing DCs, by adding four small molecular inhibitors: Y27632, PD0325901, PD173074, and PD98059 (abbreviated as YPPP), in mouse bone marrow (BM) culture with granulocyte-macrophage colony stimulating factor (GM-CSF). BM-derived DCs cultured with YPPP (YPPP-DCs) showed high responsiveness to lipopolysaccharide stimulation, resulting in increased interleukin (IL) -12 production and enhanced proliferation activity when co-cultured with naïve T cells compared with the vehicle control. RNA-seq analysis revealed an upregulation of peroxisome proliferator - activated receptor (PPAR) γ associated genes increased in YPPP-DCs. In tumor models treated with anti-programmed death (PD) -1 therapies, mice injected intratumorally with YPPP-DCs as a DCs vaccine exhibited reduced tumor growth and increased survival. These findings suggested that our method would be useful for the induction of DCs that efficiently activate effector T cells for cancer immunotherapy.